mRNA Expression of Two Colon Enzymes in Pre-Pubertal Gilts During a 42-Day Exposure to Zearalenone - Magdalena Gajęcka; Łukasz Zielonka; Maciej T. Gajęcki (Toxins, 2025)
The aim of this study was to determine whether a low dose of zearalenone (ZEN) affects the mRNA expression of the CYP1A1 (P450 cytochrome) and GSTπ1 (glutathione S-transferase) genes in the large intestine of pre-pubertal gilts. Materials: Control (C) group gilts (n = 18) received a placebo. Experimental (E) group gilts (n = 18) were orally administered 40 μg ZEN/kg body weight (BW) each day before morning feeding for 42 days. Three animals from each group were sacrificed each week of the study. Tissue samples were collected from the medial parts of the ascending colon and the descending colon on six dates. Results: Zearalenone concentrations were multiple times higher in the last three weeks of exposure, and ZEN metabolites were not detected. In phase I, CYP1A1 mRNA expression in the ascending colon was suppressed in the final three weeks of exposure, which substantially increased the ZEN concentration in the descending colon. In phase II, ZEN levels were high in the descending colon due to CYP1A1 suppression in the ascending colon. Consequently, the phase II detoxification processes could not take place due to the absence of a substrate. Conclusion: This study demonstrated that low-dose ZEN mycotoxicosis disrupts the expression of the CYP1A1 and GSTπ1 genes, which co-participate in the enzymatic biotransformation of ZEN in both examined sections of the large intestine. The above could have contributed to increased ZEN accumulation in the mucosa of the descending colon in the last three weeks of exposure.